New images and dressed bodies (2019)
As a complement of this inquire, we search for the possibility to understand the bodyas an image and the dress as a medium, as a way to apprehend the constant creationprocess that human being do with its appearance. But for that, we cannot stand on theold paradigms that define the image like something out of the man, but like somethingthat inhabits and shape him, we have to know what imply the new images and theconceptual transformations that deliver to this time